Sociology 771: Understanding Consumer Society - Schor, Juliet (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is designed to expose and train graduate students in the sociology of consumption. As such the major emphasis is on the literature in sociology, but the reading list also includes authors from related disciplines such as history, cultural studies and anthropology. Although consumption has been studied for more than a century, in the 1980s, the literature exploded, in a variety of areas, and from a number of fields. It is now large, and includes studies of the ways in which people consume media, food, cultural products, clothing and fashion, vehicles, technology, celebrity, etc. Originally the literature centered on the critiques of writers such as Marx, Veblen, Simmel, and the Frankfort school. It has since moved on to consider issues such as the ways in which consumption structures and reproduces social difference, the role of consumer practices in the constitution of culture and personal identity, how consumption becomes a site of sub-cultural resistance, the role of consumption in modernity and post-modernity, and so forth. These theoretical perspectives form the structure of the course.